2013
DOI: 10.1021/jp408517m
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Mechanism of the Water–Gas Shift Reaction on Cobalt@Gold Core–Shell Nanocluster

Abstract: We studied the mechanism of the water−gas shift reaction (WGSR; CO + H 2 O → CO 2 + H 2 ) catalyzed by Co 6 @Au 32 core−shell nanoalloy using density-functional theory (DFT) calculations to investigate the bimetallic effects on the catalytic activation. The molecular structures and adsorbate/substrate interaction energies were predicted, along with the potential energy surface constructed using the nudged elastic band (NEB) method. Our results indicated that the energetic barriers of the two hydrogen dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…The revealed mechanism of the NiIr-catalyzed CO oxidation mirrors the water–gas shift (WGS) reaction. WGS reactions catalyzed by metal carbonyl complexes have been studied experimentally, and details of the mechanism have also been elucidated by theoretical investigations. , The proposed mechanisms both involve formation of metallocarboxylic acids followed by decarboxylation to afford hydride complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The revealed mechanism of the NiIr-catalyzed CO oxidation mirrors the water–gas shift (WGS) reaction. WGS reactions catalyzed by metal carbonyl complexes have been studied experimentally, and details of the mechanism have also been elucidated by theoretical investigations. , The proposed mechanisms both involve formation of metallocarboxylic acids followed by decarboxylation to afford hydride complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The exchange-correlation energies were calculated via the generalized gradient approximation (GGA) with the Perdew-Burke-Ernzerhof (PBE) functional [85]. The valance electrons were described by 5d 10 6s 1 for Au, 4d 9 5s 1 for Pd, 2s 2 2p 4 for O and 2s 2 2p 2 for C. We used a 25 Å×25 Å×25 Å cubic supercell for all the calculations, as reported by Lin et al [86,87]. An energy cutoff of 400 eV was chosen for the plane wave expansion of the electronic eigenfunctions.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Their study revealed that the core–shell nanoclusters are highly active for CO oxidation, compared to Au(1 1 1) and Au(3 2 1) surfaces. Wu and co‐workers compared the reaction mechanism of the water gas shift reaction catalyzed by a Co 6 @Au 32 nanocluster with that catalyzed by the Au 38 cluster by employing DFT calculations . They found that the core Co atoms can control the geometry structure of the surface Au atoms and the electronic structure near the Fermi level indicating the foreign core could play an important role in the catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%